Cultural adaptation and validation of SATAQ-4 “Sociocultural attitudes towards appearance questionnaire-4” for peruvian population - Zevallos-Delzo, Carolina (2020)
Introduction: Eating disorders (anorexia and bulimia) have been increasing worldwide and nationally. Prior to the development of this disorder, adolescents' present body dissatisfaction, whose study through the ¨Tripartite Influence Model¨ gives us three main pressures: Pressure from parents, media and peers. Factors that are studied through SATAQ-4. We conduct a study to validate the Peruvian version of SATAQ-4 "Sociocultural Attitudes Toward Appearance Questionnaire-4". Methods: A cross-sectional study was carried out in 2015. It was started by culturally adapting the test. Subsequently, validity was determined through the validity of the construct, and reliability through internal consistency assessment and intra-observer reliability (test-retest). Results: We obtained a culturally adapted instrument which presented a mean greater than 3 in the Delphi method, an intraclass correlation equal to 0.83 and an internal consistency (Cronbach alpha) of 0.90. The confirmatory factor analysis supported the original five-factor structure and the convergent validity analysis (r Pearson) when compared with BSQ a correlation of 0.70. Conclusions: The instrument adequately measures the construct for which it was created and can be applied in the Peruvian university environment.